PERTIMBANGAN HAKIM TERHADAP KETERANGAN AHLI PADA TINDAK PIDANA KORUPSI DALAM PENGADAAN BARANG/JASA - Trina Yuliana; Sukmareni Sukmareni; Syaiful Munandar (Ensiklopedia of Journal, 2023)
The criminal act of corruption is any person who unlawfully commits an act of enriching himself or another person which is detrimental to state finances in article 2 paragraph 1 of law number 31 of 1999, based on article 1 number 28 of the Criminal Procedure Code states that expert testimony is information related to his expertise having a clear role in a case in a criminal act of corruption with this problem, the problem can be formulated including 1. How is the judge's consideration of the expert testimony given on the crime of corruption in the procurement of goods and services in Nagari, the decision No: 41/Pid.Sus.TPK arises. /2022/PN.Pdg ) 2. How is the application of punishment to the perpetrators of corruption in the procurement of goods and services provided by the judge in the case (Decision No: 41/Pid.Sus.TPK./2022/PN.Pdg)? This research method uses a nomative juridical approach in which the research is carried out by examining laws and regulations, aiming to provide knowledge and contributions of thought to law enforcement officials who have a duty in criminal prosecution of corruption.